Experimental characterization and numerical modelling analyses of nano-adhesive-bonded joints - Fayssal Hadjez; Brahim Necib (Fracture and Structural Integrity)
This paper presents an experimental and numerical characterization, typical for adhesive aerospace applications. The task is carrying two steps. The first consists on the analysis of a single lap joint produced by a carbon fiber fabric reinforced composite with five samples joined by injecting a nanostructure epoxy resin (Graphene 2% by weight) while five others are not. The shear tests have been carried out on the specimens with the purpose of measuring the resistance of the bonded joint, to look forward the resulting differences of structural performances. The second deals with numerical models which have been developed based on the experimental tests for adhesive joints using the finite element techniques. The numerical simulation has been expressed using the ANSYS software in order to analyze the adhesive lap joint model. It has been noted that two options have been retained in attention which deals with and without nano-adhesive. In the two alternatives, we focused on the cooling process where the adhesive single-lap joints are mainly generated. Roughly speaking, the experimental tests and the numerical model show a good agreement. Moreover, the Graphene increases the stiffness of the lap joints under rational loads charges. On the other side, the nanostructure injection in the adhesive has increased the failure as the load increase. However, this increase of failure depends on parameters such as adhesive structural features and nanostructure’s structure. Finally, we were fortunate to observe that, the reinforced adhesive nanostructure has decreased the weight.